Non-linear representation of voltage sag profiles for fault location in distribution networks - Mokhlis, Hazlie; Li, H.Y. (International Journal of Electrical Power & Energy Systems, 2011)
Fault location for distribution networks with multiple laterals would requires additional information such as from fault indicators and protective devices. As SCADA systems to provide such information are limited in 11 kV or lower voltage distribution networks, effective fault location method that only use information from a measurement at primary substation is needed. This paper presents the application of calculated non-linear voltage sag profiles and voltage sag measurement at primary substation to locate a fault in distribution networks. The proposed method firstly identifies the faulted section. From the indentified section, fault distance is calculated. The method has been tested under different fault scenarios that include various fault resistance, loading variation and data measurement errors. The results indicate the possibility of using this method to support automatic fault management system.